Intervalos de chuva sobre a eficácia de controle químico de trapoeraba (Commelina benghalensis) - Silva, Ferdinando Marcos Lima [UNESP]; Velini, Edivaldo Domingues [UNESP]; Rossi, Caio Vitagliano Santi; Corrêa, Marcelo Rocha; Negrisoli, Eduardo; Carbonari, Caio Antonio [UNESP] (My University, 2011)
The objective was to evaluate the influence of intervals without rain after the application of mixtures of carfentrazone-ethyl and glyphosate in the effectiveness of control on Commelina benghalensis. The experimental design was completely randomized with 11 treatments, with two rates of the mixture carfentrazone + glyphosate, 30 + 960 (with sequential application at 21 DAA of the mixture 20 + 960 g ha-1) and 50 + 960 g ha-1 of a.i. and five intervals of precipitation 0, 3, 6, 12 and 24 hours after application (HAA), with four repetitions, being an absolute check. The mixture was applied in post-emergence, then was carried out simulations of rain in the predetermined intervals. Were assessed the effectiveness of visual control (0 to 100 %) at 7, 14, 21, 28, 35 and 42 DAA. The results were compared by t test, with 10 % level of probability. It was observed that the application of the herbicides carfentrazone + glyphosate in the evaluated rates and even in the sequential application did not have control of C. benghalensis. The results with the second application are greater than the single application, and the best absorption of the mixture carfentrazone + glyphosate by C. benghalensis when there is a bigger interval between application and rainfall occurrence, and is necessary a minimum interval of 6 HAA for intermediate control of C. benghalensis.

Objetivou-se avaliar a influência de intervalos sem chuva após a aplicação de misturas de carfentrazone e glyphosate na eficácia de controle sobre Commelina benghalensis. O delineamento experimental foi inteiramente casualizado com 11 tratamentos, sendo duas dosagens da mistura carfentrazone-ethyl + glyphosate, 30 + 960 (com aplicação sequencial aos 21 DAA da mistura 20 + 960 g ha-1) e 50 + 960 g ha-1 de i.a e cinco intervalos de precipitação 0, 3, 6, 12 e 24 horas após a aplicação (HAA), com quatro repetições, sendo uma testemunha absoluta. A mistura foi aplicada em pós-emergência, em seguida realizou-se simulações de chuva nos intervalos predeterminados. Foram feitas avaliações visuais da eficácia de controle (0 a 100 %) aos 7, 14, 21, 28, 35 e 42 DAA.Os resultados foram submetidos à análise de variância pelo teste F e as médias comparadas pelo teste t em nível de 10 % de probabilidade. Observou-se que a aplicação dos herbicidas carfentrazone + glyphosate nas doses avaliadas e mesmo na aplicação seqüencial não apresentaram controle da C. benghalensis. Os resultados com a segunda aplicação são superiores à aplicação única, sendo a melhor absorção da mistura de carfentrazone + glyphosate pela C. benghalensis quando há um maior intervalo entre a aplicação e ocorrência de chuva e que é necessário intervalo mínimo de 6 HAA para o controle intermediário da C. benghalensis.
Rain intervals on the effectiveness of dayflower (Commelina benghalensis) chemical control
Keywords: Herbicide; Rain; Weed; Chuva; Herbicida; Planta daninha